Seaports and development in tropical Africa - Hoyle, B. S.; Hilling, D. (London: Macmillan, 1970)
The essays in this volume have been brought together to emphasize the important role of seaports in the economic growth of underdeveloped areas, and to demonstrate the increasing interest now focused upon this problem by geographers in tropical Africa.
Includes bibliographical references.
ne 5/03/2018
Loans
Keywords: Harbors; Seaports and development; Africa